Diagnosis of the state of economic security of agricultural enterprises in the context of challenges and extraordinary circumstances - Trusova, Natalia; Трусова, Наталя Вікторівна (Запоріжжя: ТДАТУ, 2025)
The components of economic security form the general attributes of effective production and expansion of own resources, which ensure the activation of economic potential based on the use of the latest IT technologies with temporal and spatial dynamics. This necessitates the use of measurable indicators that allow for the assessment of exogenous (external economic conditions of agricultural enterprises) and endogenous (internal) factors of economic efficiency (the structure of the property complex, productivity, and profitability of agricultural enterprises). Therefore, the priority of our research is to increase the level of economic security of agricultural enterprises as a system that embodies a state of stable equilibrium of components in the trajectory of resource flow when the environment in which they operate changes, taking into account the restructuring of the factors affecting the security system.
Keywords: security system; economic